2020
DOI: 10.2147/ijn.s271159
|View full text |Cite
|
Sign up to set email alerts
|

<p>Synthesis, Characterization, and Toxicity Assessment of Pluronic F127-Functionalized Graphene Oxide on the Embryonic Development of Zebrafish (<em>Danio rerio</em>)</p>

Abstract: Background In the current literature, there are ongoing debates on the toxicity of graphene oxide (GO) that demonstrate contradictory findings regarding its toxicity profile. As a potential drug carrier, these findings are very concerning due to the safety concerns in humans, as well as the dramatic rise of GO being excreted into the environment. Therefore, there is an imperative need to mitigate the potential toxicity of GO to allow for a safer application in the future. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 68 publications
1
19
0
1
Order By: Relevance
“…Several studies have revealed that the modification of copolymers can improve the biocompatibility of GBNs in vivo . For example, when the unoxidized graphene surface mosaic is pluronic, the toxicity in vivo is further lower than GO . Moreover, the modification of the copolymer offers a safe and reliable option for the application of GBNs in the biomedical field.…”
Section: Biocompatibility Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed that the modification of copolymers can improve the biocompatibility of GBNs in vivo . For example, when the unoxidized graphene surface mosaic is pluronic, the toxicity in vivo is further lower than GO . Moreover, the modification of the copolymer offers a safe and reliable option for the application of GBNs in the biomedical field.…”
Section: Biocompatibility Evaluationmentioning
confidence: 99%
“…For example, when the unoxidized graphene surface mosaic is pluronic, the toxicity in vivo is further lower than GO. 195 Moreover, the modification of the copolymer offers a safe and reliable option for the application of GBNs in the biomedical field.…”
Section: Biocompatibility Evaluationmentioning
confidence: 99%
“…With the further application of GO, its biotoxicity and safety have become the focus of research. A study reported that nano-scale GO has a dose-dependent toxic effect on zebrafish embryonic development (15). Some scholars had found that the oral administration of GO nanoparticles causes various behavioral and developmental defects in the offspring of drosophila (16).…”
Section: Introductionmentioning
confidence: 99%
“…All these features make zebrafish attractive as a model organism in studying toxicology with simplicity by assessing their developmental and morphological changes. Furthermore, zebrafish embryos have also been widely used, and have been considered highly effective in screening the toxicity of nanomaterials [ 27 , 28 ], as well as phytochemicals extracted from plants, such as Piper sarmentosum [ 29 ]. The salient features of the embryos, which are their greater sensitivity to undesired harmful effects and their transparent nature, make it easy for the embryos to be analyzed for the effects of toxicants on their organs, such as the heart, brain, liver, kidney, and others.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it allows direct observation of the periods of development and the assessment of the endpoints of toxicity. Testing using nanomaterials on zebrafish embryos also allows several parameters to be varied such as concentration, size, chemical composition, and time of exposure [ 27 , 28 , 30 ]. A previous study using zinc oxide nanoparticles on zebrafish embryos was not only able to assess embryo toxicity, but was also able to analyze the antioxidant defence system, ROS, and DNA damage [ 31 ].…”
Section: Introductionmentioning
confidence: 99%